National Health Interview Survey, 1994: Year 2000 Objectives Supplement ([Verlag nicht ermittelbar], 1997)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1994 [ICPSR 6724]), including sex, age, race, education, family income, limitations on school activities, family relationship, and relationship to reference person. The Year 2000 Supplement also contains items on seven selected topics that relate to the Department of Health and Human Services (HHS) Year 2000 Health Objectives: environmental health, tobacco, occupational safety and health, heart disease, clinical and preventive services, family, and firearms. Among the variables included in this supplement are respondent's type of residence, whether household air was tested for radon, current smoking status, tobacco use, employer's smoking policies, current employer assistance to employees to control weight, employer-sponsored exercise programs, and presence of screening tests and health education programs at the workplace. This supplement also includes questions about blood pressure, salt intake, hypertension, most recent physical exam, frequency of physical exams, presence of a sexually transmitted disease (STD), usage of illegal drugs, and gynecological issues. Variables in the family section cover number of family members in the household, nutrition, discussions with family members regarding nutrition and eating habits, exercise and sports, safety and injury prevention, cigarette smoking and tobacco use, drinking alcoholic beverages, sexual behavior, and use of illegal drugs. Respondents were also queried about whether there were children aged 10-17 in the household, whether sex education was taught at home and/or school, and whether children were involved in a sex education program conducted by a youth or a religious program for children. Variables relating to firearms include the number and types of firearms in the household, place firearms were kept, whether firearms were loaded, and whether ammunition was kept.